Study of the Perturbation in Temperature Profile of an AGR Fuel Pin for Surface Roughness of Cladding by CFD Simulation in Ansys Fluent - Nishat, Sadek Hossain; Farha, Farhana Islam; Sahadath, Md Hossain (Dhaka University Journal of Applied Science and Engineering, 2023)
The surface roughness of nuclear fuel cladding plays a crucial role in the thermal-hydraulic response of the Advanced Gas Cooled reactor (AGR). In the present work, the change in the temperature distribution from an isolated AGR fuel rod to primary coolant due to cladding roughness was studied by computational fluid dynamics (CFD) simulation in Ansys Fluent software. Square transverse ribs of the various pitch to height ratios _p / k_ were considered as the surface roughness. Radial temperature profiles from fuel to coolant were generated. Lower fuel temperature was found for the fuel rod with a rough cladding surface as compared to the smooth cladding surface. The peak fuel temperature was determined and found to decrease with decreasing values of _p / k_ . Temperature drop across the fuel and from fuel to coolant was also studied. DUJASE Vol. 7(1) 9-15, 2022 (January)